Clinical manifestations and pathogenesis of cutaneous lymphomas: current status and future directions. (26th October 2016) - Rubio‐Gonzalez, Belen; Zain, Jasmine; Rosen, Steven T.; Querfeld, Christiane
Summary: The primary cutaneous lymphomas are a heterogeneous group of T‐, Natural Killer‐ and B‐ cell neoplasms with a wide range of clinical and pathological presentations, and with very different prognoses compared to systemic lymphomas. Recent studies have shown that the skin microenvironment, which is composed of various immune cell subsets as well as their spatial distribution and T‐cell interactions through different chemokines and cytokines, has an important role in the development and pathogenesis of cutaneous lymphomas and has assisted in the development of novel and more effective immunotherapies. The following review will focus on the major subtypes of primary cutaneous lymphomas, including the clinical and histological patterns, molecular hallmarks, and current and future treatment strategies.